Postpartum lumbopelvic pain could be SAPHO syndrome: a case report - Weiwei, Zheng; Junhong, Zhang; Rong, Zhang (Frontiers in Immunology, 2025)
BackgroundSynovitis–acne–pustulosis–hyperostosis–osteitis (SAPHO) syndrome is a rare autoimmune disorder. The involvement of spinal and sacroiliac joint in SAPHO syndrome closely resembles the manifestations of postpartum lumbopelvic pain (LPP).Case presentationWe report a case of a patient whose primary symptom was postpartum LPP, with recurrent episodes lasting 10 months without relief. Unexpectedly, she was diagnosed with SAPHO syndrome in the 11th month when she sought medical attention for severe palmoplantar pustulosis rather than LPP. After combined treatment with Tofacitinib citrate tablets and Etoricoxib tablets, all the pain symptoms disappeared.ConclusionFor postpartum patients with concurrent palmoplantar scaling and recurrent LPP unresponsive to treatment, clinicians should consider SAPHO syndrome as a potential diagnosis.